Analysis of Determining Order Quantity of Spare Parts in Oil and Gas Well Service Activities Using Monte Carlo Simulation - Tikupadang, Lakun; Rusdiansyah, Ahmad (Newinera Publisher, 2024)
This research aims to explore the analysis of determining the order quantity of spare parts in well service activities in the oil and gas (Migas) industry using the Monte Carlo simulation approach. The Migas industry requires efficient inventory management to maintain operational smoothness, but this need must be balanced with efforts to minimize excessive storage costs. Therefore, it is important to determine the optimal order quantity to meet operational needs while avoiding unnecessary inventory accumulation. The Monte Carlo simulation method was chosen because of its ability to address uncertainty in inventory analysis, allowing for modeling variations in demand, delivery lead times, and other factors affecting inventory management. It is expected that this approach will provide a better understanding of how decisions regarding the order quantity can be made more effectively in the context of well service activities in the Migas industry. The main expectation of this research is the development of a model that can assist Migas companies in optimizing the management of their spare parts inventory. Thus, it is hoped that this research will make a significant contribution to improving operational efficiency, reducing storage costs, and increasing customer service levels in the Migas industry. It is also hoped that the results of this research will pave the way for the development of inventory management strategies that are more adaptive and responsive to dynamic business environments.